Beneficial effect of hydrogen in aluminum oxide deposited through the atomic layer deposition method on the electrical properties of an indium–gallium–zinc oxide thin-film transistor. Issue 2 (2nd April 2016) - Nam, Yunyong; Kim, Hee-Ok; Cho, Sung Haeng; Hwang, Chi-Sun; Kim, Taeho; Jeon, Sanghun; Ko Park, Sang-Hee
ABSTRACT: Described herein is the role of hydrogen in aluminum oxide (Al2 O3 ) gate dielectrics in amorphous indium–gallium–zinc oxide (a-InGaZnO or a-IGZO) thin-film transistors (TFTs). Compared to a-IGZO TFTs with a low-temperature (150°C) Al2 O3 gate dielectric, a-IGZO devices with a high-temperature (250–300°C) Al2 O3 gate dielectric exhibit poor transistor characteristics, such as low mobility, a high subthreshold slope, and huge hysteresis. Through DC and short-pulsed current–voltage ( I – V ) measurements, it was revealed that the degradation of the transistor performance stems from the charging and discharging phenomenon at the interface traps located in the interface between the a-IGZO semiconductor and the Al2 O3 gate insulator. It was found that the low-temperature Al2 O3 atomic layer deposition processed film contains a higher density of hydrogen atoms compared to high-deposition-temperature films. The study results show that a high concentration of hydrogen atoms can passivate the defect sites in the interface and bulk, which produces excellent transistor characteristics. This study demonstrated that hydrogen has a beneficial effect on the defect passivation for oxide TFTs.